Intraoperative Fascia Tension as an Alternative to Component Separation. A Prospective Observational Study - Niebuhr, Henning; Aufenberg, Thomas; Dag, Halil; Reinpold, Wolfgang; Peiper, Christian; Schardey, Hans Martin; Renter, Marc Alexander; Aly, Mohamed; Eucker, Dietmar; Köckerling, Ferdinand; Eichelter, Jakob (Frontiers in Surgery, 2021)
Incisional hernias are common late complications of abdominal surgery, with a 1-year post-laparotomy incidence of about 20%. A giant hernia is often preceded by severe peritonitis of various causes. The Fasciotens® Abdomen device is used to stretch the fascia in a measurably controlled manner during surgery to achieve primary tension-free abdominal closure. This prospective observational study aims to clarify the extent to which this traction method can function as an alternative to component separation (CS) methods. Methods: We included data of 21 patients treated with intraoperative fascia stretching in seven specialized hernia centers between November 2019 and August 2020. Results: Intraoperatively-measured fascial distance averaged 17.3 cm (range 8.5–44 cm). After application of diagonal-anterior traction >10 kg for an average duration of 32.3 min (range 30–40 min), the fascial distance decreased by 9.8 cm (1–26 cm) to an average 7.5 cm (range 2–19 cm), which is a large effect (r = 0.62). The fascial length increase (average 9.8 cm) after applied traction was highly significant. All hernias were closed under moderate tension after the traction phase. In 19 patients, this closure was reinforced with mesh using a sublay technique. Conclusion: This method allows primary closure of complex (LOD) hernias and is potentially less prone to complications than component separation (CS) methods.